Ethics and knowledge: a debate that never ends - Marín, Alfredo L.; García, Mario A. (Revista Gregoriana de Ciencias de la Salud, 2025)
This editorial reflects on the enduring tension between scientific-technological progress and the ethical considerations that should accompany it. Through historical and current examples—such as artificial intelligence in medical diagnostics, gene editing, or clinical trials involving vulnerable populations—the authors raise fundamental questions about moral responsibility in the production of knowledge. The role of Human Research Ethics Committees (CEISHs) is emphasized, especially in the Ecuadorian context, where their consolidation in universities is crucial for ensuring the integrity of academic projects. The editorial emphasizes the importance of linking Knowledge Integration Projects with ethical review processes, particularly when human participants are involved. It concludes by asserting that ethics in science must go beyond regulations and be understood as a personal and collective commitment to guide knowledge toward the common good.